PENYULUHAN BELA LINGKUNGAN LAUT PADA NELAYAN PANGGONG DI MEULABOH - Jun Musnadi; Rinawati Rinawati; Zulfadhli Zulfadhli; Chairiyaton Chairiyaton (Universitas Teuku Umar, 2019)
Panggong Village is located on the coast of the city of Meulaboh where many residents earn a living as fishermen who often bring instant food supplies when they go out to sea and throw plastic containers and cans into the sea as rubbish where they find fish. The purpose of this activity is to provide counseling to increase the knowledge and awareness of the fishermen so that they throw garbage in its place. Community service activities begin with the preparation, outreach, outreach and discussion about waste management. The result of this community service activity was an increase in understanding from the level of 71.05 percent before the training was held to 96.71 percent after the implementation of the program and the awareness of the fishing community regarding waste disposal.